2017
DOI: 10.1159/000469663
|View full text |Cite
|
Sign up to set email alerts
|

In utero Exposure to Germinated Brown Rice and Its GABA Extract Attenuates High-Fat-Diet-Induced Insulin Resistance in Rat Offspring

Abstract: Background: Numerous studies have reported on the influence of diet on insulin resistance. Our study provides insight into the effect of germinated brown rice (GBR) and γ-aminobutyric acid (GABA) on early environment-driven programming and susceptibility to insulin resistance in rat offspring. Methods: Male rat offspring from female Sprague-Dawley rats fed with a high-fat diet (HFD) alone, HFD + GBR, or HFD + GABA extract throughout pregnancy and lactation were weaned 4 weeks after delivery and followed up for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…However, increased IRS mRNA expression was observed in the BR groups, suggesting an adequate flow of insulin signalling pathways. This is consistent with the studies by Shen et al [ 64 ] and Adamu et al [ 68 ], both of whom reported upregulation of IRS mRNA expression in the BR groups of the rat model.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, increased IRS mRNA expression was observed in the BR groups, suggesting an adequate flow of insulin signalling pathways. This is consistent with the studies by Shen et al [ 64 ] and Adamu et al [ 68 ], both of whom reported upregulation of IRS mRNA expression in the BR groups of the rat model.…”
Section: Discussionsupporting
confidence: 93%
“…Impairment in the insulin signalling pathway results in a deficiency of insulin stimulation of glucose uptake leading to IR [ 68 ]. Existing evidence suggests that serine/threonine phosphorylation attenuates insulin signalling by reducing the extent of tyrosine phosphorylation of IRS proteins [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Afterward, both ends of the bilimbi were cut off, and it was sliced into thin pieces. The sliced bilimbi was placed in a bowl and soaked for one (1) hour. Following the soaking period, the bilimbi was rinsed three times to remove any impurities and set aside for later use as shown in Figure 1.…”
Section: A Preparation Of Bilimbimentioning
confidence: 99%
“…20–22 Furthermore, GBR could affect genetic programming in offspring rats to improve insulin sensitivity and alleviate HFD-fed metabolic disorders. 23 Previous experiments in our laboratory showed that oryzanol (100 mg kg −1 ) administration can regulate the expression of genes in lipid metabolism, inflammatory responses, and improve obesity in HFD-fed mice. 24 In addition, the supplementation of octacosanol reduced dyslipidemia in HFD-fed mice by regulating signaling pathways related to lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%